Control de las cuentas por pagar de la Empresa “Radiadores Troya” de la ciudad de Duran, período 2019-2020. - Onofre Cabrera, Jhon Ariel (2023)
This case study was conducted with the objective of analyzing the economic situation through financial tools to determine the most influential factors in the profitability of the company "Radiators Troya" in the city of Babahoyo. The purpose of this project is to measure the financial health of the business during an economic and national health crisis caused by the Covid-19 pandemic. This was accomplished by analyzing the organization's accounts payable systems and determining the overall financial status of the company. With that information, conclusions were drawn about its overall financial status and performance. An inductive-deductive approach was used in this study, as the results of the study were analyzed separately to then draw general conclusions about the research process. Analytical methods are also used, as the causes and consequences of problematic situations are investigated to achieve a better understanding of the investigated context.